The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1002/(sici)1097-4628(19990404)71:14<2401::aid-app12>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and thermal characterization of epoxy-amine systems

Abstract: The curing behavior of epoxy resins was analyzed based on a simple kinetic model. We simulated the curing kinetics and found that it fits the experimental data well for both diglycidylether of bisphenol A-4,4Ј-methylene dianiline and diglycidylether of bisphenol A-carboxyl-terminated butadiene acrylonitrile-4,4Ј-methylene dianiline systems. The kinetic results showed the curing of epoxy resins involves different reactive process and reaction stages, and the value of activation energy is dependent on the degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 7 publications
0
19
1
Order By: Relevance
“…We have reported previously about the variation of reaction activation energy with conversion in the conventional epoxy resins, [24] where the constant activation energy related to the autocatalytic reaction was in the conversion range from 0.3 to 0.6. It was in good agreement with the a c value from the Flory-Stockmayer equation.…”
Section: Kinetic Analysismentioning
confidence: 99%
“…We have reported previously about the variation of reaction activation energy with conversion in the conventional epoxy resins, [24] where the constant activation energy related to the autocatalytic reaction was in the conversion range from 0.3 to 0.6. It was in good agreement with the a c value from the Flory-Stockmayer equation.…”
Section: Kinetic Analysismentioning
confidence: 99%
“…These values are slightly higher compared to values reported earlier for the same resin. 22 The decrease in E a with increasing conversion has been observed earlier and has been attributed to the formation of hydroxyl groups from the reaction between the amine and the epoxy. 29 The hydroxyl groups facilitate epoxy ring opening and thereby catalyze the curing reaction.…”
Section: Curing Kinetics Of S-20 Modified Epoxy Resinmentioning
confidence: 61%
“…The copolymer is blended with a thermosetting epoxy system composed of diglycidyl ether of bisphenol A (DGEBA) and 4,4'-methylenedianiline (MDA) at the stoichiometric ratio. The ultimate glass transition temperature (T g∞ ) of this resin has been reported to be in between 165°C 22 and 175°C 23 implying that complete curing of the pure resin is expected after sufficient time at an isothermal temperature of at least 115-125°C. The isothermal cure kinetics were analyzed by Differential Scanning Calorimetry (DSC) and the morphology by simultaneous synchrotron small and wide angle X-ray scattering (SAXS and WAXD) in combination with Transmission Electron Microscopy (TEM).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…But the dependence of the activation energy on conversion in the early stage of cure for DGEBA/LCCAn systems is very different from DGEBA/DABP system, as is shown that the activation energy exhibited an increase during the early curing stage which may be related to the formation of liquid crystalline phase, which is verified in POM study. Some research has also found that the LC phase has an influence on the curing reaction [6,[25][26][27]. Furthermore, the values of E a for DGEBA/LCCAn systems are not very different.…”
Section: Curing Kinetics Analysismentioning
confidence: 99%